Multiple autoimmunity and epitope spreading in monozygotic twins - Esperanza Avalos-Díaz (Elsevier, 2021)
We report clinical, serologic, and immunogenetic studies of a set of monozygotic male twin patients who develop autoimmune thyroiditis and vitiligo associated with the HLA-DRB1*04-DQB1*03:02 and HLA-DRB1*03-DQB1*0201 haplotypes. The patients had detectable anti-thyroid and anti-melanocyte autoantibodies. A critical review is presented regarding the role of MHC II molecules linked to clinical manifestations of various autoimmune diseases displayed in a single patient, as is the case in the twin patients reported here.